근육통을 주소로 내원한 그레이브스병 - 홍성빈; Sung Bin Hong; 박영주; Young Ju Park; 오윤주; Yoon Ju Oh; 김영완; Young Wan Kim; 김성기; Sung Ki Kim; 김미림; Mi Rim Kim; et al. (The Korean journal of medicine, 2001)
Graves' disease is commonly associated with a variety of muscle abnormalities from muscle weakness, paralysis to exophthalmopathy. There are several reports of Graves disease associated with polymyositis and myasthenia gravis. It is generally uncommon that muscle enzyme is increased in patients with hyperthyroidsm without polymyositis. We report thyrotoxic myopathy presented as myalgia without muscle weakness but with increased muscle enzyme, which was improved by anti-thyroid drug. A 33 year-old man developed severe proximal myalgia and headache. The creatinine kinase level was elevated. But there was no specific finding in electromyography. Muscle biopsy showed increased number of mitochondria and decreased glycogen content. There was no inflammatory cell infiltration. Diagnosis of hyperthyroidism due to Graves' disease was made, followed by the treatment with prothiouracil 300 mg per day. Five day after the treatment, myalgia improved, and serum CPK was decreased. He never complain myalgia after thyroid function was normalized.(Korean J Med 61:173-177, 2001)